Implikasi Debt Trap Diplomacy dalam Proyek Belt and Road Initiative di Sri Lanka: Analisis Perspektif Keamanan Tradisional - Feodor Farrel Sulistyo (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the phenomenon of Debt Trap Diplomacy in Sri Lanka as a manifestation of economic statecraft within the framework of the Belt and Road Initiative (BRI), as well as its implications for the country's sovereignty and traditional security. The research employs a qualitative descriptive-analytical approach through a case study of the acquisition of Hambantota Port, drawing upon Kenneth Waltz's neorealist theory as the primary analytical framework, supplemented by the concepts of geoeconomics and traditional security.The findings indicate that China's involvement in Sri Lanka through BRI infrastructure financing mechanisms gradually created a structure of economic dependency, culminating in the transfer of control over Hambantota Port through a 99-year lease agreement to the Chinese state-owned enterprise China Merchants Port Holdings in 2017. Although empirical evidence suggests that Sri Lanka's debt crisis was also driven by domestic governance failures and fiscal mismanagement, the transfer of control over this strategic maritime infrastructure has generated significant security implications, both for Sri Lanka and for the broader stability of the Indian Ocean region. From a neorealist perspective, this phenomenon reflects China's systematic efforts to address its strategic vulnerabilities through the projection of non-military power, while also demonstrating that, in the modern era, the erosion of territorial sovereignty can occur through economic instruments without the need for armed confrontation.